Studies on the synthesis of low molecular weight, one‐dimensional polyanilines prepared by fast emulsion polymerization using (n‐dodecylbenzenesulfonic acid)/HCl emulsifiers. Issue 4 (3rd August 2012) - Wu, Yi‐Jhen; Ho, Ko‐Shan; Cheng, Yu‐Wei; Chao, Liang; Wang, Yen‐Zen; Hsieh, Tar‐Hwa; Ho, Tsung‐Han; Han, Yu‐Kai
Abstract Low molecular weight polyaniline nanotubes were prepared by fast emulsion polymerization in the presence of both n‐dodecylbenzenesulfonic acid (DBSA) and HCl(aq). The anilinium monomers associated with DBSA emulsifiers were found to self‐arrange into strands of associated cylindrical micelles before polymerization, as monitored by their optical activity and optical image. In the presence of some HCl(aq), the monomer‐associated cylindrical micelles expanded and the polymerization rate could be speeded up. It was found that the low molecular weight (viscosity‐averaged molecular weight) polyaniline obtained can easily lead to the formation of highly conductive, one‐dimensional nanotubes or nanofibers monitored by the variation of optical activities and λmax of the UV–visible–near IR spectra during polymerization. The DBSA/HCl ratio played an important role in the eventual properties and morphologies of the one‐dimensional polyanilines, which can be illustrated by conductivity, SEM and transmission electron microscopy measurements. The resultant one‐dimensional polyaniline nanotubes can be arranged into a layered structure by orientation, illustrated by AFM and wide‐angle X‐ray diffraction. © 2012 Society of Chemical Industry